A Novel Piezoelectric Ceramic Actuator with Scissoring Composite Vibration for Medical Applications - Jingjing Yang (Applied Sciences, 2019)
This paper presents a novel scissoring composite actuator which can successfully degenerate longitudinal vibration into scissoring vibration at actuator tips for potential medical applications. The proposed actuator consists of back mass, multilayer piezoceramic stack, front mass with netted pre-stress structure and beam. The actuator is driven by only a small axially poled multilayer piezoceramic stack. Moreover, a special symmetrical grooved structure is designed at the beam end to convert longitudinal driving vibration into opposite bending vibrations at the beam tip, resulting in scissoring-type composite vibration. The converted scissoring vibration concentrates on the beam tip without any deflection along other parts, which is highly desirable for narrow-spaced medical operations. The proposed design principle is demonstrated by structural analysis and verified by different types of finite element modeling (FEM) simulations, including Eigen frequency analysis, harmonic analysis, and transient analysis. The results reveal the design effectiveness of the actuator’s structure on scissoring-type mode excitation. Finally, a prototype of the proposed piezoelectric actuator is fabricated and tested, rendering superior performance and highly reliable mode conversion. The proposed actuator exhibits potential for advanced medical applications.